2015
DOI: 10.1108/jfbm-04-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of family ownership and control on equity-based compensation

Abstract: Purpose – Small public family firms apply contracting differently given the peculiar motivations of founding families and the degree to which they monitor operations. The purpose of this paper is to examine the effects of family ownership, control, and CEO dividends on CEO incentive compensation. Design/methodology/approach – The sample consisted of 194 firms, covering about 40 percent of the relevant S&P SmallCap 600 firms. Employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…After summarizing these findings, we describe the accomplishments and shortcomings of extant research and use reflexivity and creative synthesis to set the stage for advancing a family science theoretical framework in which to center future research on executive compensation. Baek and Fazio (2015) Agency theory 1,532 public U.S. firms CEO incentive compensation Family ownership is negatively related to the propensity to adopt equity-based compensation plans and to the ratio of such compensation to total pay. The CEO's dividend income relative to the CEO's total compensation was negatively related to the propensity to adopt an equity-based compensation plan.…”
Section: Executive Compensation In Family Firms: a Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…After summarizing these findings, we describe the accomplishments and shortcomings of extant research and use reflexivity and creative synthesis to set the stage for advancing a family science theoretical framework in which to center future research on executive compensation. Baek and Fazio (2015) Agency theory 1,532 public U.S. firms CEO incentive compensation Family ownership is negatively related to the propensity to adopt equity-based compensation plans and to the ratio of such compensation to total pay. The CEO's dividend income relative to the CEO's total compensation was negatively related to the propensity to adopt an equity-based compensation plan.…”
Section: Executive Compensation In Family Firms: a Reviewmentioning
confidence: 99%
“…These focused on how compensation packages are developed, what types of incentives are likely to be offered to executives in family firms or the proportion of variable pay in the compensation package, and what the consequences are. Most studies agree that family businesses make less use of incentive contracts (Baek & Fazio, 2015; Memili et al, 2013; Speckbacher & Wentges, 2012) and have lower levels of incentive pay (Baek & Fazio, 2015; Bhabra & Hossain, 2018; Mazur & Wu, 2016; McConaughy, 2000; Tsao et al, 2015) when compared with nonfamily businesses. These results are generally explained through the higher agency costs in nonfamily firms due to severe owner-manager conflicts.…”
Section: Executive Compensation In Family Firms: a Reviewmentioning
confidence: 99%
“…But while the typical pay of nonmanagerial employees may be higher in nonfamily (relative to family) firms, both theory and empirical evidence from studies of executive pay (McConaughy, 2000;Baek & Fazio, 2015) suggest that family (relative to nonfamily) firms may still be less likely to attempt to shift the risk in the effort-pay bargain onto employees (Eisenhardt, 1989). From an agentic perspective, despite the productivity benefits potentially associated with more tightly linking pay to effort or performance (Eisenhardt, 1989), family ownermanagers may view incentive-based pay as placing greater restrictions on their ability to allocate a larger share of reward resources to fellow family members (Chrisman et al, 2014;Chua, Chrisman, & Bergiel, 2009).…”
Section: Pay Formmentioning
confidence: 99%
“…The authors explain that employment relationships between family members are characterized by trust, reciprocal altruism, and shared values, which can serve as a substitute for incentive contracts, since they help to align interests between the parties. Baek and Fazio (2015) also observed that family firms design agency contracts with less incentive mechanisms for family CEOs, especially when they receive material dividends. Interestingly, the authors offer a distinct rationale to explain their results, suggesting that family firms deviate from the tenets of agency contracting, as suggested by Schulze et al (2001) and Gomez-Mejia et al (2001).…”
Section: Related Literature Executive Pay and Incentive Compensation mentioning
confidence: 99%
“…They articulate utility theory and the theory of compensating wage differentials to sustain that family employees derive utility from working in their own family firm, in complement to wages and nonpecuniary job characteristics. Baek and Fazio (2015) also found out that family firms are less prone to use incentives in agency contracts, especially when the family CEO is paid material dividends. The authors interpreted their results as evidence that family firms do not closely conform to the tenets of agency contracting in compensation, as suggested by Schulze et al (2001) and Gomez-Mejia et al (2001).…”
Section: Introductionmentioning
confidence: 99%